FISSURING DUE TO INUNDATION OF COAL MINES AND ITS HYDRODYNAMIC IMPLICATIONS - Mokhov A.V. (My University, 2007)
Inundation of coal mines can be accompanied by unexpected water inflow and inrush to mine workings of neighboring coal-producing enterprises. In this case, it is common for mine water to inflow through barrier and shaft pillars that are waterproof during exploitation.